Evaluation of Resonant Column Dynamic Testing Devices. - Skoglund,George R.; Marcuson,William F. , III; Cunny,Robert W. (1975)
Resonant column tests were performed by six participants in a program designed to evaluate results from various devices. The participants were Dr. V. P. Drnevich, Dr. B. O. Hardin, Dr. R. D. Woods, Shannon and Wilson, Inc., the U.S. Army Engineer Cold Regions Research and Engineering Laboratory, and the U.S. Army Engineer Waterways Experiment Station. Tests were performed on fine sand and clayey silt. Each participant was given more or less identical samples of material and specific instructions intended to keep the test conditions as near identical as possible. Differences in shear and compression miduli ranged from minus 19 to plus 32 percent of the average. These differences could be explained largely by differences in unit weight and specimen preparation techniques. No systematic differences were noted because of differences apparatus used.